Использование современных телевизионных технологий «виртуальная студия» для создания «виртуальной лекции» В. А. Морванюк, A. B. Азаренков - Азаренков, В. И.; Морванюк, В. А.; Азаренков, A. B. (УАДО, 2002)
My lecture is about new contemporary technologies in television. I am telling you’re about process, which make “virtual studio”. In my lecture you can hear how real man be situated in room which make at computer graphics software. In second part of my report I am try to make ‘‘virtual lecture” for leach students, with help of technologies, which use in contemporary television.
Keywords: «виртуальная студия»; “virtual studio”